2016
DOI: 10.1093/annonc/mdw417
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of melanoma brain metastases treated with stereotactic radiosurgery and anti-PD-1 therapy, anti-CTLA-4 therapy, BRAF/MEK inhibitors, BRAF inhibitor, or conventional chemotherapy

Abstract: In our institutional analysis of patients treated with SRS and various systemic immunologic and targeted melanoma agents, significant differences in distant MBM control and OS are noted. Prospective evaluation of the potential synergistic effect between these agents and SRS is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
90
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 26 publications
12
90
1
3
Order By: Relevance
“…Our findings indicate that these immune checkpoint inhibitors are effective for controlling not only the primary melanoma but also distant metastases to the brain. Several previous reports have shown a regional immunomodulatory effect and penetration of novel systemic agents into the brain [8,11,12,15,18,20,21,23]. The present results might indicate passage of these agents thorough the bloodbrain barrier in melanoma patients, thereby leading to suppression of new metastases to the brain.…”
Section: Discussionsupporting
confidence: 67%
“…Our findings indicate that these immune checkpoint inhibitors are effective for controlling not only the primary melanoma but also distant metastases to the brain. Several previous reports have shown a regional immunomodulatory effect and penetration of novel systemic agents into the brain [8,11,12,15,18,20,21,23]. The present results might indicate passage of these agents thorough the bloodbrain barrier in melanoma patients, thereby leading to suppression of new metastases to the brain.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, micrometastases elsewhere in the brain may contribute to an underlying endogenous immune response. The study on SRS plus nivolumab mentioned earlier showed an extended survival of 5/7 patients with resected metastases, whereas only 3/19 patients without resection were alive at 24 months (132). This strongly supports that irradiation of the resected cavity is indeed capable of eliciting an antitumor immune response and furthermore suggests that the tumor cell load may be an important factor in controlling residual disease.…”
Section: Potential Of Combining Iort With Immune Therapy For Bmmentioning
confidence: 92%
“…However, although one trial included four patients who underwent prior resection of metastases before SRS to the cavity plus IPI (131), none have a priori addressed therapy of a purely resected population. Combining SRS with an anti-PD-1 antibody (nivolumab) has only been described in a single study on 73 lesions in 26 patients with median 9.4 months follow-up (132), including patients with resected lesions. Overall, local control (82% at 12 months) was comparable to conventional treatments, while distant control (53%) was higher than for other treatments.…”
Section: Combining Srs With Immune Therapy For Bmmentioning
confidence: 99%
See 1 more Smart Citation
“…Median OS was 11.8 and 12.0 months, respectively, in patients receiving nivolumab for unresected disease. Median OS was not reached in patients treated in the resected setting [26].…”
Section: Nivolumabmentioning
confidence: 94%